Ausstellungskünstler : Kult und Karriere im modernen Kunstsystem. - Bätschmann, Oskar (Köln : Dumont Buchverlag Köln, 1997)
Abbé, Grégoire ; Acconci, Vito ; Adam, Nicolas-Sébastien ; Adam, Robert ; Ahlers-Hestermann, Friedrich ; Andersen, Hans Christian ; Angivillier, Charles-Claude ; Apollinaire, Guillaume ; Arensberg, Louise & Walter ; Arp, Hans (Jean) ; Artaud, Antonin ; Astruc, Zacharie ; Aurier, G.-Albert ; Avedon, Richard ; Bacon, Francis ; Bahr, Hermann ; Balzac, Honoré ; Banks, Thomas ; Barker, Robert ; Barrault, Emile ; Barry, James ; Bart, Alfred H. ; Bartolozzi, Francesco ; Baruzzi, Cincinnato ; Baselitz, Georg ; Bashkirtseff, Marie ; Batoni, Pompeo ; Baudelaire, Charles ; Bazille, Frédéric ; Beckmann, Max ; Beethoven, Ludwig von ; Behrens, Peter ; Benetton, Giulians ; Bergeret, Pierre-Nolasque ; Bernard, Emile ; Bernini, Gian Lorenzo ; Bertall ; Bertaux, Mme Léon ; Betti, Salvatore ; Beuys, Joseph ; Bindesboll, Michael Gottlieb ; Blanc, Charles ; Blavatsky, Helena P. ; Bleyl, Fritz ; Böcklin, Arnold ; Bode, Arnold ; Bodmer, Johann Jakob ; Boileau-Despréaux, Nicolas ; Boizot, Louis Simon ; Bonaparte, Joseph ; Bonaparte, Lucien ; Bongard, Willi ; Bonheur, Rosa ; Bonnard, Pierre ; Boothby, Brooke ; Bos, Jean-Baptiste Du ; Boucher, François ; Bourdieu, Pierre ; Bourgeois, Louise ; Bowness, Alan ; Bowyer, Robert ; Boydell, John ; Boydell, Josiah ; Brancusi, Constantin ; Brandoin, Charles ; Brinckmann, Maria ; Bruyas, Alfred ; Buchon, Max ; Bullock, William ; Buonarroti, Michelangelo ; Buren, Daniel ; Burke, Edmund ; Burkhardt, Jacob ; Burty, Philippe ; de Cabanes, Jean ; Cadart, Alfred ; Caillebotte, Gustave ; Calas, Nicolas ; Calder, Alexander ; Canova, Antonio ; Capote, Truman ; Carracci, Annibale ; Carstens, Asmus Jakob ; Cassatt, Mary ; Castagnary, Jules-Antoine ; Castelli, Leo ; de Caylus, Anne Claude ; de Cervantes, Miguel ; Cézanne, Paul ; Chagall, Marc ; etc.
boek